1998
DOI: 10.1038/nm0398-309
|View full text |Cite
|
Sign up to set email alerts
|

A structure-based approach to designing synthetic CD8α peptides that can inhibit cytotoxic T-lymphocyte responses

Abstract: CD8 molecules function as co-receptors on cytotoxic T lymphocytes (CTLs), interacting with a nonpolymorphic region of the major histocompatibility complex (MHC) class I a3 domain on antigen-presenting cells. Analogues were designed from a structural model of the mouse CD8a molecule to identify surfaces involved in CD8 function. Peptides were screened for in vitro biological activity on alloreactive CTLs, and analogue SC4 (p54-59) was found to be inhibitory during both the generation and effector stages. SC4 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Membrane-bound CD8aa negatively regulates coreceptor-dependent or coreceptor-independent TCR activation regardless of a productive interaction between its extracellular domain and the antigen-presenting MHC class I molecules (Cawthon et al, 2001). This is in sharp contrast to the potent capacity of soluble CD8aa (sCD8aa) molecules or CD8a-derived peptides to block the interaction between MHC and the CD8ab coreceptor (Choksi et al, 1998;Kern et al, 1999;Sewell et al, 1999). The interference by sCD8aa results in the inhibition of CD3z tyrosine phosphorylation and indicates that the blocking by sCD8aa targets the earliest stage of activation consistent with inhibition of p56 lck activation.…”
Section: Cd8aa Corepressor Functionmentioning
confidence: 93%
“…Membrane-bound CD8aa negatively regulates coreceptor-dependent or coreceptor-independent TCR activation regardless of a productive interaction between its extracellular domain and the antigen-presenting MHC class I molecules (Cawthon et al, 2001). This is in sharp contrast to the potent capacity of soluble CD8aa (sCD8aa) molecules or CD8a-derived peptides to block the interaction between MHC and the CD8ab coreceptor (Choksi et al, 1998;Kern et al, 1999;Sewell et al, 1999). The interference by sCD8aa results in the inhibition of CD3z tyrosine phosphorylation and indicates that the blocking by sCD8aa targets the earliest stage of activation consistent with inhibition of p56 lck activation.…”
Section: Cd8aa Corepressor Functionmentioning
confidence: 93%
“…It has also been suggested that interference with a small number of the multimolecular complexes might alter the quality of the T cell response from an agonist to partial agonist (38,39). Similar mechanisms may explain how a soluble CD8 peptide corresponding to amino acids 54 -59 of CD8 extends the survival of allogeneic skin grafts in vivo (40).…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structures of unbound homodimeric CD8 extracellular domain (ECD) and the CD8 /MHC class I complexes indicate that the CD8αα homodimer interacts through all three CDRs with the α3 domain of MHC Class I molecule [47,48]. Using the structural model of murine CD8α as the template in computer simulations, Choksi et al suggested that the CDR-2 like region of CD8 exhibited a folding pattern that is partially independent of the rest of the molecule providing an ideal target for drug design [49]. Screening of multiple peptides from the CD8-CDR-2 loop region identified an octa-peptide (C 51 SSHNKP 57 C) that significantly inhibited cytolytic T cell responses and prolonged skin allograft survival [49].…”
Section: B Cd8 Inhibitorsmentioning
confidence: 99%